A Quality Improvement Intervention Aimed to Reduce Patient Cycle Time at a Student-Run Clinic - Shaw, William; Vaz-Ayes, Melissa; Mathelier, Michael; Byrd, Angelica; Kronlage, René; Stanley, Amy; Holland, Carolyn (Journal of Student-Run Clinics, 2025)
Background: The Equal Access Clinic Network offers free primary and specialty care services to underinsured or uninsured individuals. Literature highlights overall patient satisfaction with experiences at Student-Run Free Clinics (SRFCs) with the exception of long wait times. The Seventh Day Adventist Equal Access Clinic, one clinic within the network that focuses on a predominantly Spanish-speaking patient demographic, currently experiences an average appointment time of 115 minutes. This project aimed to reduce appointment times from 115 to 90 minutes, approximately a 20% decrease, over a 5-month period. Methods: The intervention used was a Plan-Do-Study-Act (PDSA) cycle, a method for continuous improvement that involves planning a change, testing it on a small scale, studying the results, and then acting based on the findings. This PDSA cycle focused on optimizing the order of patient visits based on complexity. A triage system was implemented, allowing patients with simpler concerns to be seen sooner to establish a more efficient workflow. Results: The main outcome measure of this project was average appointment time. At the end of the intervention, the average visit time was around 124 minutes which was an unwanted increase from the baseline of 115 minutes. Several other variables confounded the results such as number of patients, number of volunteers, arrival time of providers, and physicians’ familiarity with the operations of the SFRC. Conclusion: The aim was not achieved throughout the implementation of PDSA cycle 1. Several factors contributed to both the success and failure of the intervention on appointment time during specific clinic nights. Regardless, a triage system may still be beneficial and investigated further in the future. This paper explores how to approach quality improvement in a SFRC which can serve as a model to benefit other clinics.